The Ethics of Labour-Management Relations - Briefs, Goetz (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1951)
SummaryIn this article, the Author describes the growth of "business ethics" — partial ethics very often conflicting with integral community ethics, — their use and abuse by businessmen at large and their acceptance by unions as a practical medium for discussion with, and victory over employers. Strong pressures have proven successful to unions: Capitalism is no longer "taboo". But, if power is to be the decisive factor, what is ahead ? Labour is likely to "come into its own". Does this potential domination of Labour differ really from other forms of totalitarianism ? There lies a saving grace, for deliberate decisions may again be made by Management and Labour. Enemy ethics must disappear. Integral ethics must govern Labour-Management relations. These relations are not ruled by competition alone, nor by power alone. Either they comply with justice, or they end in chaos, organized. This article constitutes a challenge to all of us.